2019
DOI: 10.1111/bjd.18151
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive objective skin measurement methods for rosacea assessment: a systematic review

Abstract: Summary Background Rosacea assessment and therapy monitoring can be challenging to standardize, as most clinical evaluation systems are prone to interobserver variability and not always validated. Therefore, objective, reliable and preferably noninvasive measurement tools are needed. Objectives To give insight into available noninvasive imaging techniques and biophysical methods in rosacea by performing a systematic review. Methods PubMed, Embase, Cochrane and Web of Science databases were searched until 1 Sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 129 publications
(472 reference statements)
0
34
1
1
Order By: Relevance
“…This suggests that the pathogenesis of rosacea cannot be entirely explained by Demodex, and mites could be one of multiple factors inducing follicular inflammation. Compared to earlier RCM studies calculating Demodex density in rosacea (8,9,(11)(12)(13)47), we measured low mite numbers, while follicle amounts were very similar (8,11). These differences could be explained by the fact that we excluded follicles with unclear content from the mite count (Figure 4(b)).…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…This suggests that the pathogenesis of rosacea cannot be entirely explained by Demodex, and mites could be one of multiple factors inducing follicular inflammation. Compared to earlier RCM studies calculating Demodex density in rosacea (8,9,(11)(12)(13)47), we measured low mite numbers, while follicle amounts were very similar (8,11). These differences could be explained by the fact that we excluded follicles with unclear content from the mite count (Figure 4(b)).…”
Section: Discussioncontrasting
confidence: 52%
“…Historically, RCM has been mainly used for the diagnosis of (non-)melanoma skin cancer (3)(4)(5)(6), but it also has promising potential in the evaluation of inflammatory skin diseases (7). Some knowledge has already been gained with the detection and quantification of Demodex mites in rosacea (8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…5 Various methods to objectify erythema have already been tested in dermatological research. 7 These studies showed that quantified erythema values correlate well with clinical scores, both in rosacea, [11][12][13][14][15]17,18 and in other inflammatory skin diseases. 25,26 Despite their promising value, none of these proposed methods have so far been implemented in daily clinical practice.…”
Section: Interobserver Concordancementioning
confidence: 98%
“…Various noninvasive techniques have already been used to quantify redness in rosacea, for example, spectrophotometry and computer-aided image analysis (CAIA). 7 Nevertheless, they have some limitations. With spectrometry, erythema is measured in only one point, questioning representativeness of the entire face.…”
Section: Introductionmentioning
confidence: 99%
“…It is often used for identifying pigmented lesions, differentiating benign and malignant tumors and determining non‐melanocytic skin tumors 9 . For a long time, the Demodex mites, microscopic parasites which normally inhabit human facial sebaceous follicles, are always considered to be causative factors of rosacea 10 . But there has been long raised a question: Which one comes first, Demodex or rosacea?…”
Section: Introductionmentioning
confidence: 99%